Canada's election: Harper glides past Martin and towards power. (Economist, 2006)
In leading the Conservatives to the brink of power for the first time since 1993, Stephen Harper has tapped a new political mood in Canada ahead of the election scheduled for January 23, 2006. He has done so in part through his own ruthless decision to move the Conservatives to the political center on a host of issues, but he has been helped by the bumbling, bungling weariness of the Liberals and of Prime Minister Paul Martin. In a 2004 general election the Liberals managed to win by painting Harper as an extreme social conservative, but in this campaign the 46-year old economist has crafted an effective mix of traditional conservatism and reassuring moderation.